Efektivitas Bokashi Daun Kelapa Sawit (Elaeis guineensis Jacq) Terhadap Produksi Kacang Kedelai (Glycine max (L.) Merr.) di Pasaman Barat - Nursyahra; Muhammad Rizki; Rizki (Biotropic : The Journal of Tropical Biology, 2020)
The low production of soybeans in the West Pasaman district is due to severeal factors, including the lack of community knowledge in soybean farming which results in less productive yields obtained by farmer and the high use of inorganic fertilizers continuously resulting in less productive soil. This study was experimental research using a completely randomized design (CRD). The treatments given were 6 treatments and 5 replications, the treatments used were 15 gram TSP (A treatment) as control treatments, 300 gram bokashi (B treatment), 400 gram bokashi (C treatment), 500 gram bokashi (D treatment), 600 gram bokashi (E treatment), 700 gram bokashi (F treatment). The data obtained were analyzed by analysis of variance and then continued by LSD test at α level of 5%. Observed parameters were the number of planting seeds and weight of 50 seeds per plant. The results of this study indicated that bokashi fertilizer had no significant effect on the number of seeds but it had significant effect on the weight of 50 seeds and the best result was found in B treatment (300 gram bokashi/polybag). This research had environmental conditions with temperatures of 30 – 340 C, environmental humidity of 63 – 80%, wind speeds of 0,2 to 2,8 m/s, and soil pH of 5,4 to 7,0.